Islamism & Democracy: A Gender Analysis on PKSâs Application of Democratic Principles and Values - Octavia, Lanny (Al-Jamiah Research Centre, 2012)
The increasing popular support for Islamist parties in democratic countries incites public suspicion concerning whether the Islamistsâ participation in procedural democracy guarantees their commitment for substantial democracy, which in principle requires equality of rights among citizens regardless of their religion and gender. Indeed, gender politics often appears at the centre of the lslamist agenda, as they seek to construct a new moral order based on a conservative gender perspective. A greater concern arises on whether the Islamists will eventually lead society towards democracy or, conversely, towards theocracy. In Indonesia, the Prosperous Justice Party (Partai Keadilan Sejahtera/PKS) shows a remarkable development and significant electoral achievement. Some observers viewed that PKS is opportunistically using democratic means to âhijackâ it for their Islamist agenda waiting for when political power is in their hands. Others believe PKSâs involvement in real politics will, in the end, lead to a âgradual secularisationâ of their Islamist agenda. Based on a gender analysis, this paper examines whether PKSâs fulfillment of the formalist criteria of democracy is compatible with their application of democratic principles and values.[Semakin menguatnya dukungan terhadap partai Islam memincu kecurigaan publik yang mempertanyakan apakah partisipasi kalangan islamis dalam demokrasi prosedural menjamin komitmen mereka bagi tegaknya demokrasi substansial, demokrasi yang mensyaratkan kesetaraan bagi semua orang tanpa terkecuali. Sebenarnya, agenda politik gender yang didengungkan oleh kalangan islamis tidak bisa dilepaskan dari perspektif konservatif mereka mengenai relasi gender. Pertanyaannya kemudian, apakah yang mereka agendakan akan berlabuh pada pemantapan demokrasi atau –sebaliknyaââÂâ menuju teokrasi. Di Indonesia, Partai Keadilan Sejahtera (PKS) adalah satu-satunya partai Islam di Indonesia yang berhasil berkembang pesat dan mampu mendulang suara secara signifikan. Bagi beberapa pengamat, PKS merepresentasikan partai Islamis yang berhasil âmenunggangiâ demokrasi untuk memperjuangkan agenda islamis mereka. Ini akan tampak jelas jika PKS berhasil menjadi partai penguasa. Kendati demikian, beberapa kalangan lainnya berkeyakinan bahwa keterlibatan PKS dalam politik demokratis akan âmensekulerkanâ agenda islamis mereka. Dengan analisis gender, tulisan ini hendak menjawab apakah kriteria formal mengenai nilai dan prinsip demokrasi yang melekat pada PKS sejalan dengan apa yang mereka praktekkan.]